2023
DOI: 10.25259/sni_1133_2022
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation-induced gastroparesis: A case report

Anusha Manjunath,
Chirag Goel,
Archit Bharathwaj Baskaran
et al.

Abstract: Background: Spinal cord stimulation (SCS) involves the utilization of an implantable neurostimulation device, stereotypically used in the treatment of patients with chronic neuropathic pain. While these devices have been shown to have significant clinical benefits, there have also been documented potential complications, including the risk of infection, fractured electrodes, electrode migration, and lack of symptom improvement. In addition, there has been minimal documentation on gastrointestinal (GI) side ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Sporadic cases documented that SCS is associated with gastrointestinal symptoms (Table 1 ). Thoracic SCS is associated with both diarrhea [ 6 ] and constipation [ 7 , 9 ], which suggests that SCS changes sympathetic/parasympathetic balance according to stimulation parameters (frequency, intensity, polarity, and targeted area). To the best of our knowledge, there are no previous reports of gastrointestinal symptoms associated with lower thoracic SCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sporadic cases documented that SCS is associated with gastrointestinal symptoms (Table 1 ). Thoracic SCS is associated with both diarrhea [ 6 ] and constipation [ 7 , 9 ], which suggests that SCS changes sympathetic/parasympathetic balance according to stimulation parameters (frequency, intensity, polarity, and targeted area). To the best of our knowledge, there are no previous reports of gastrointestinal symptoms associated with lower thoracic SCS.…”
Section: Discussionmentioning
confidence: 99%
“…SCS is effective for visceral pain when the midline dorsal columns of thoracic levels are targeted [1][2][3][4]. Although transient and reversible, studies have reported SCS-associated unfavorable gastrointestinal symptoms such as nausea, diarrhea, or constipation [5][6][7][8][9]. While these symptoms suggest autonomic neuromodulation of gastrointestinal systems, therapeutic effects have been demonstrated only for the treatment of irritable bowel syndrome through T5-8 stimuli [10][11][12].…”
Section: Introductionmentioning
confidence: 99%